DEVELOPMENT OF ANDROID-BASED “MBARENGI” STATISTICS E-MODULE AS AN INNOVATION FOR STATISTICS LEARNING MEDIA WITH HYBRID LEARNING - Astuti, Cindy Cahyaning; Wiguna, Akbar; Latifa, Fitri Nur; Olvyya, Amaydhi (PATTIMURA UNIVERSITY, 2022)
The learning process is closely related to the interaction between educators and students. In order to facilitate the learning process, educators are required to make learning more innovative in order to be able to encourage students to study hard and be able to follow the learning process well. One of the innovations that can be done in the learning process is innovation in learning media. Learning media is one of the components of learning that has an important role in teaching and learning activities, especially in the transition after the Covid 19 pandemic. The use of smartphones can be one of the innovations of learning media by using Android-based e-modules. This research is development research or called Research and Development (R&D) using the ADDIE development model (Analyze, Design, development, Implementation, and Evaluation). The Android-based